Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Targeted regulation and extraction mechanism of rare earth elements and thorium during the decomposition of rare earth concentrates - Xiaowei Zhang; Likai Zang; Feng Guo; Yanhong Hu; Jinxiu Wu; Wenjun Fan; Jianguo Cui; Na Li; Xiaodong Wang; Ruifeng Ma (Minerals Engineering, 2026)

Vanadium(IV)-chlorodipicolinate alleviates hepatic steatosis via the AMPK/PGC-1α/CPT1a axis - Rulong Chen; Yufan Liu; Yuanli Wang; Fang Zhang; Jinkui Ma; Wei Cui; Wenjun Ding (BioMetals, 2026)

Understanding eco-hydrological processes in winter wheat croplands through physically consistent modelling - Linlin Li; Yunfei Wang; Aofan Cui; Xinyu Mao; Wenjun Zhao; Wei Li (Theoretical and Applied Climatology, 2026)

A physically consistent coupling framework of the lattice Boltzmann method and the hybrid finite-discrete element method via a corrected immersed moving boundary scheme for improved fluid–solid interaction modeling - Wenjun Cui; Zhijun Wu; Xuehai Wu; Xiangyu Xu; Erkang Zhou (Computers and Geotechnics, 2026)

12-Year straw and manure amendments control rill scouring through enhanced humification and aggregate stabilization - Qianjin Liu; Wenjun Sun; Abdulvahed Khaledi Darvishan; Leila Gholami; Yun Wang; Hao Cui; Wenliang Wei; Hanyu Zhang; Shutang Liu (Soil and Tillage Research, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Dry–wet cycle may trigger the catastrophic landslide in Junlian on February 8, 2025 - Wenjun Jia; Tao Wen; Ningsheng Chen; Raoxi Cui; Qiao Luo (Landslides, 2026)

Rapid quantitative real-time analysis and visual detection of Escherichia coli in meat by direct PMAxx-VPCR - Jiaqi Cui; Tingting Zhao; Wenjun Song; Huilin Li; Yan Chen; Rong Chen (Food Control, 2026)

Crosstalk with the cholinergic pathway may be responsible for chlorpyrifos-induced reproductive toxicity in fish - Aoxue Wang; Yujia Yan; Yuyao Jiang; Yanru Guan; Zexin Wen; Shengli Zhou; Yanmei Xu; Haisong Cui; Miqi Jin; Wenjun Gui; Shuying Li (Aquatic Toxicology, 2026)

Mesoscale Convective Systems over South Asia: Unraveling climatology, land-ocean differences and environmental drivers - Debjit Paul; Sarvesh Dubey; Wenjun Cui (Climate Dynamics, 2025)

Simultaneously sampling sulfonamide antibiotics (SAs) and endocrine disrupting chemicals (EDCs) in aqueous environment by the DGT passive sampler with a novel composite binding gel - Jing Wang; Peng Zhang; Wenjun Chen; Yaqing Cui; Linke Ge; Yinping Hou (Journal of Environmental Chemical Engineering, 2025)

Progress in therapeutic applications of microalgae and their bioactive compounds - Xinrong Geng; Jinqi Qu; XiaoFei Yin; Qi Wang; Wenjun Li; Hongli Cui; Song Qin (Algal Research, 2025)

Spatial distribution and seasonal variations of typical UV filter and insect repellent personal care products in a coastal resort area in Qingdao, China - Jianan Li; Chunyao Zhao; Jiajia Li; Duan Zheng; Qinlin Yang; Peiyang Zhang; Xiaoheng Wang; Yihua Xiao; Zhenchao Zhou; Erping Cui; Wenjun Xie (Environmental Pollution, 2025)

The intensity of cell surface charge defines the malignancy of cancer cells - Shuyuan Hu; Jingyao Chen; Yihui Hu; Wenjun Le; Pengbo Zhang; Wenwen Jia; Quanhu Sun; Tao Chen; Wei Bao; Zheng Cui; Bingdi Chen (Chemical Engineering Journal, 2025)

Associations of long-term exposure to PM2.5 and its constituents with children renal function: a national retrospective study in China - Siwen Yu; Chunxia Cui; Wei Wu; Lianlong Yu; Yiya Liu; Qijiong Zhu; Zhiqing Chen; Shangfeng Yang; Yi Lin; Jianxiong Hu; Guanhao He; Xiaomei Dong; et al. (Environmental Research, 2025)

Characterization of physicochemical properties of different epigallocatechin-3-gallate nanoparticles and their effect on bioavailability - Lidan Cui; Baogui Liu; Zhihui Ling; Kehong Liu; Simin Tan; Zhihua Gong; Wenjun Xiao (Food Chemistry, 2025)

Mapping of identity by descent reveals genes shaping morphology and biological traits in the cultivated lettuce varieties during the long-term crossbreeding - Qianqian Zhang; Bo Cui; Xinyu Dong; Wenjun Lv; Xueying Xie; Yujue Wang; Zhongxu Guo; Just Jensen (Theoretical and Applied Genetics, 2025)

Water-induced phase separation ionogel for Recyclable information encryption - Ying Cui; Yunlong Liu; Qian Wang; Shuhong Li; Wenjun Wang; Xiaochen Dong (Chemical Engineering Journal, 2025)

Historical inventories and future scenarios of multiple hazardous air pollutants (HAPs) emissions from the iron and steel production industry in China - Junqi Yang; Hezhong Tian; Zhiqiang Fu; Xiaoxuan Bai; Kun Wang; Wenjun Liu; Yiping Lu; Yu Zhou; Hongyan Zhao; Jiangyu Cui; Qinwei Du (Science of The Total Environment, 2025)

High-yield magnetosome production of Magnetospirillum magneticum strain AMB-1 in flask fermentation through simplified processing and optimized iron supplementation - Yu Wang; Zhengyi Liu; Wenjun Li; Hongli Cui; Yandi Huang; Song Qin (Biotechnology Letters, 2024)

Pt-promoted mesoporous Beta zeolite catalysts for n-Hexane isomerization with enhanced selectivity to dibranched isomers - Pengzhao Wang; Tingting Chen; Zihui Qiu; Wenjun Yao; Pengpeng Liu; Yongze Zhang; Yu Song; Qingyan Cui; Xiaojun Bao (Fuel, 2024)

H2O2 self-supplied CuFeOx nanosystem as fenton-like reaction agents for endogenous/exogenous responsive synergetic antibacterial therapy - Lei Zhao; Yawen Chen; Qinglin Wei; Xinyi Lv; Ying Cui; Wenjun Wang; Xiaozhou Mou; Xuejiao Song; Xiaochen Dong; Yu Cai (Chemical Engineering Journal, 2024)

The transcription factor MdERF023 negatively regulates salt tolerance by modulating ABA signaling and Na+/H+ transport in apple - Cui Chen; Zhen Zhang; Yingying Lei; Wenjun Chen; Zhihong Zhang; Hongyan Dai (Plant Cell Reports, 2024)

Understanding the energy poverty in China: chronic measurement and the effect of the digital economy - Li Sun; Wenjun Cui; Yang Li; Yueli Luo (Environment, Development and Sustainability, 2024)

Diurnal variation in short‐ and long‐duration precipitation within the Dabie Mountain region in Central China - Chao Li; Chunguang Cui; Xingwen Jiang; Xiaofang Wang; Shenming Fu; Wenjun Cui; Andrew H. Berrington; Jing Sun; Peiting Liu (International Journal of Climatology, 2024)
Diurnal variation in regional precipitation in Central and East China has been broadly identified in previous study. This study focused on clarifying not only the differences in the diurnal variation concerning the local precipitation occurred in the Dabie Mountain (DBM) region and the regional precipitation occurred through the middle‐lower reaches of the Yangtze River Basin, but also the association mechanism between diurnal variation in local precipitation with differing duration and diurnal modulation of ambient circulations driven by large‐scale background synoptic force or local‐scale orographic force of the DBM. It was found that cases of short duration precipitation (SDP, duration

Rapid colorimetric and fluorescence identification of Pinelliae Rhizoma and adulterate Rhizoma Typhonii Flagelliformis using direct-LAMP assay - Huilin Li; Jiaqi Cui; Hongling Chen; Hongying Li; Yuchen Xie; Wenjun Song; Rong Chen (Food Chemistry, 2024)

Antibacterial properties and mechanism of nanometer zinc oxide composites - Ying Wang; Jiawei Liu; Ting Wang; Li-Zhi Liu; Chengcheng Tian; Ye Cui; Wenjun Shao; Xia Hua; Ying Shi; Yuanxia Wang (Food Packaging and Shelf Life, 2023)

Cold stress causes liver damage by inducing ferroptosis through the p38 MAPK/Drp1 pathway - Yujie Huang; Kun Xiong; Aiping Wang; Zejun Wang; Qi Cui; Hongchen Xie; Tian Yang; Xu Fan; Wenjun Jiang; Xiaoling Tan; Qingyuan Huang (Cryobiology, 2023)

Strategical design of bridged vanillic Schiff-bases as jet fuel antioxidants - Ji Mi; Cui Ye; Yongsheng Guo; Wenjun Fang (Fuel, 2023)

Correction: Characteristics of land-subsidence evolution and soil deformation before and after the Water Diversion Project in Beijing, China - Kunchao Lei; Fengshan Ma; Beibei Chen; Yong Luo; Wenjun Cui; Yi Zhou; Fang Tian; Te Sha (Hydrogeology Journal, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Modeling Geothermal Heat Extraction-Induced Potential Fault Activation by Developing an FDEM-Based THM Coupling Scheme - Zhijun Wu; Wenjun Cui; Lei Weng; Quansheng Liu (Rock Mechanics and Rock Engineering, 2023)

Can agricultural heritage systems keep clean production in the context of modernization? A case study of Qingtian Rice-Fish Culture System of China based on carbon footprint - Wenjun Jiao; Wenchao Cui; Siyuan He (Sustainability Science, 2023)

Drivers of aboveground biomass shift with forest stratum in temperate forest of North China - Qinyuan Zhang; Qing Zhang; Yinuo Zhai; Wenjun Yang; Yan Zhang; Hongxiang Liu; Kun Zhang; Xiao Liu; Kening Cui; Hui Wang; Peiming Zheng; Renqing Wang (Science of The Total Environment, 2023)

Degradation of contaminants of PPCPs by photocatalysis for water purification: Kinetics, mechanisms, and cytotoxicity analysis - Yanei Xue; Wenjun Sun; Penghui Shao; Yixing Yuan; Fuyi Cui; Wenxin Shi (Chemical Engineering Journal, 2023)

Effects of South-to-North Water Diversion Project on groundwater and land subsidence in Beijing, China - Kunchao Lei; Fengshan Ma; Beibei Chen; Yong Luo; Wenjun Cui; Long Zhao; Xinhui Wang; Aihua Sun (Bulletin of Engineering Geology and the Environment, 2023)

Buffer effect of MgO on Na2SO3 to stabilize S(IV) for the enhancement in simultaneous absorption of NOx and SO2 from non-ferrous smelting gas - Wenjun Huang; Sichao Li; Hongbin Wang; Peng Cui; Haomiao Xu; Can Cheng; Zan Qu; Naiqiang Yan (Environmental Science and Pollution Research, 2022)

High-precision potassium isotope analysis using the Nu Sapphire collision cell (CC)-MC-ICP-MS - Wenjun Li; Mengmeng Cui; Qiqi Pan; Jing Wang; Bingyu Gao; Shanke Liu; Meng Yuan; Benxun Su; Ye Zhao; Fang-Zhen Teng; Guilin Han (Science China Earth Sciences, 2022)

Characteristics of land-subsidence evolution and soil deformation before and after the Water Diversion Project in Beijing, China - Kunchao Lei; Fengshan Ma; Beibei Chen; Yong Luo; Wenjun Cui; Yi Zhou; Fang Tian; Te Sha (Hydrogeology Journal, 2022)

Effect of DAOA genetic variation on white matter alteration in corpus callosum in patients with first-episode schizophrenia - Wenjun Su; Tianyuan Zhu; Lihua Xu; Yanyan Wei; Botao Zeng; Tianhong Zhang; Huiru Cui; Junjie Wang; Yuping Jia; Jinhong Wang; Donald C. Goff; Yingying Tang; et al. (Brain Imaging and Behavior, 2021)

Nucleoprotein phosphorylation site (Y385) mutation confers temperature sensitivity to influenza A virus due to impaired nucleoprotein oligomerization at a lower temperature - Weinan Zheng; Liang Cui; Minghui Li; Yun Li; Wenhui Fan; Limin Yang; Jing Li; Lei Sun; Wenjun Liu (Science China Life Sciences, 2021)

Study on mechanical and permeability characteristics of nickel-copper-contaminated soil solidified by CFG - Qiang Wang; Man Li; Jingdong Yang; Jinyang Cui; Wenjun Zhou; Xiaoliang Guo (Environmental Science and Pollution Research, 2020)

Fate of Phthalic Acid Esters (PAEs) in Typical Greenhouse Soils of Different Cultivation Ages - Xianxu Li; Wenjun Liu; Cui Zhang; Peipei Song; Jun Wang (Bulletin of Environmental Contamination and Toxicology, 2020)

Optimum design of level monitoring points for land subsidence - Yong Luo; Beibei Chen; Kunchao Lei; Ruilin Hu; Chao Ye; Wenjun Cui (Bulletin of Engineering Geology and the Environment, 2019)

Fipronil induces apoptosis and cell cycle arrest in porcine oocytes during in vitro maturation - Wenjun Zhou; Ying-Jie Niu; Zheng-Wen Nie; Yong-Han Kim; Kyung-Tae Shin; Jing Guo; Xiang-Shun Cui (Apoptosis, 2019)

Using the DNDC model to simulate the potential of carbon budget in the meadow and desert steppes in Inner Mongolia, China - Xuan Wu; Xiaoming Kang; Wenjun Liu; Xiaoyong Cui; Yanbin Hao; Yanfen Wang (Journal of Soils and Sediments, 2018)